Ceria-Promoted Titanium Dioxide (CeO2/TiO2) Nanocomposites for Efficient Phenol Removal under Advanced Oxidation Processes (AOPs) - Farah Guitouni; Ilhem Rekkab-Hammoumraoui; Sanaa El Korso; Mohamed Sassi; Chewki Ziani-Cherif (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
In this study, a series of x %CeO2/TiO2 (x= 1, 2, 3, 5 and 10) catalysts were successfully synthesized with Ce(NO3)3.6H2O as precursor via a simple wetness impregnation method. The resulting samples were characterized by XRD, FTIR, surface area and pore volume measurements, Raman spectroscopy, SEM, and UV-Vis -DRS. These catalysts were used for the degradation of the phenol through three types of advanced oxidation processes (AOPs), namely the heterogeneous Fenton process (photocatalyst/H2O2), the photocatalysis process (photocatalyst/UV), and the photo-Fenton process (photocatalyst/UV/H2O2). The 10 ‎%‎ CeO2/TiO2 catalyst showed superior degradation efficiency of 99.05 ‎%‎, when used in the heterogeneous photo-Fenton process. To determine the optimal conditions for phenol degradation, using the heterogeneous photo-Fenton process, the effects of parameters such as photocatalyst dosage, initial pH, phenol concentration, H2O2 volume, and temperature were investigated. The optimal conditions were as follows: 0.1 g of catalyst, 0.6 mM of hydrogen peroxide, a reaction temperature of 25 °C, an initial pH of 8, an initial phenol concentration of 30 ppm, and a reaction time of 240 minutes. The impact of radical scavengers (such as p-benzonquinone, silver nitrate, EDTA-2Na and propan-2-ol) on degradation efficiency was also studied. For all three oxidation processes, phenol photodegradation could be described by the pseudo-first-order kinetics according to the Langmuir-Hinshelwood model. Furthermore, the catalysts could be easily recovered from the reaction solution by centrifugation and reused for five cycles without significant loss of activity. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).